Technology research and Design, Manufacturing of the Small Power Freeze-Dry System for Production of High Quality Food - Nguyễn Tấn Dũng (Journal of Technical Education Science, 2007)
At present, technological processing and preserving foods are very various and abundant, it’s enough demand for human in Viet Nam and export passing other countries in the world to have profit from that processing food. However, the methods for processing and preserving that were not only a waste of level of vitamine, natural pigments (colour) and natural smells but also denatured proteine (change characteristics of proteine of it), lipid was oxidized, etc. The result was decreased in nutrient of food and food was not enough quality. For this reason, informations in this paper will introduce the most modern method for processing and preserving foods that is method to freeze-dry, this method drys food in distance of temperature from -450 C to 400C not to change characteristics of foods is not denatured, lipid is not oxidized, vitamine and natural pigments (colour) and natural smells is not destroyed. At the moment, The Technology of Sublimation (Lyophilization) still isn’t developed into perfection as a result the other day, the scientist in the world will be researching into technical lyophilization and researching to transfer heat in environmental vacuum by heat radiations, because of in the fact that in environmental vacuum can not transfer by heat conducting or thermal convection, the heat radiations must have micro-wavelength because it will be accumulated a macro-energy and increased the capability to transfer heat.